Dimensional control in formed steel panels for ship hull - Zhang, Chi (2008)
The manufacturing process of hull plates includes hull design, definition, fairing, modeling, lofting, cutting, and forming in sequence. At the lofting stage, the hull surface is discomposed into a finite number of plates, each of which is cut from flat stocks and formed to fit the faired hull surface. For the efficient and accurate hull plate forming, the information from design to manufacturing should be systematized and integrated. Hence, management of the information plays an important role in the computer integrated manufacturing (CIM) of formed panel for ship hull.